Gender Differences in a Youth Physical Activity Intervention: Movement Levels and Children's Perceptions. - McGovern, Jen; Drewson, Staci R.; Hope, Andrea; Konopack, James F. (American Journal of Health Education)
Background: Sedentary behavior is a public health issue associated with obesity and other chronic health problems. The need for interventions is especially pressing for girls, who have lower levels of physical activity (PA) than boys do, and who are more likely to be overweight and to experience negative emotional states as they approach adolescence. Purpose: This study used a mixed-methods approach to examine gender differences in PA levels and perceptions of movement opportunities in an afterschool intervention. Methods: Data were collected from 22 children (4th-5th grade) who participated in a 15-week afterschool PA intervention (30, 1 hour sessions). PA levels were measured using accelerometers and perceptions of PA were gathered via focus groups. Results: Boys moved significantly more than girls based on total accelerometer counts (310,617 vs. 279,766, t = − 3.63, p <.01) and step counts per session (2,297 vs. 2,100, t = − 3.40, p <.01). Gender differences in PA perceptions emerged regarding competency and relationships. Discussion: Understanding gendered differences in PA perceptions are crucial to developing effective afterschool PA interventions. Translation to Health Education Practice: Interventions that enhance PA enjoyment for girls should incorporate self-efficacy of physical skills, cooperative style games, and activities that offer social interactions. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI)